Nutrition of Wafer Produced from Silage of Cabbage Vegetable Waste and Rice Brain With Different Packaging Types - Triani Adelina; Anwar Efendi Harahap; Arsyadi Ali; Fitri Harianti (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The wafer packaging process is  necessary in maintaining quality during storage and transportation. This study aimed to evaluate the nutritional quality of the wafers produced by silage from various combinations of cabbage vegetable waste and rice bran which were stored using different types of packaging. This research method used factorial design (4x2) with 2 replications. The first (A) factor was the composition of the silage of cabbage and rice bran waste (A0: 100% cabbage waste; A1: 75% cabbage waste + 25% rice bran; A2: 50% cabbage waste + 50% rice bran; A3: 25% cabbage waste + 75% rice bran), while second factor (B)was the type of packaging (B0: plastic packaging; B1: gunny sack packaging). The results showed that the composition of the silage of cabbage and rice bran waste had a very significant effect (P <0.01) Dry matter, crude protein, crude fiber and BETN content of wafers produced. The type of packaging was also had a very significant effect(P <0.01) on dry matter, crude protein, and crude fiber content of the wafer and there was an interaction between materials composition of silage and types of packaging in producing wafer ash. The conclusion  of this research is that the substrate composition of 25% cabbage vegetable waste + 75% rice bran and gunny sack packaging could maintain the nutritional quality of the wafers.